Phosphorylation tunes elongation propensity and cohesiveness of INCENP’s intrinsically disordered region - Kemmer, Isabel M.; Aponte-Santamaria, Camilo; Schmidt, Lisa; Hedtfeld, Marius; Iusupov, Adel; Musacchio, Andrea; Gräter, Frauke (Journal of molecular biology, 2022)
The inner centromere protein, INCENP, is crucial for correct chromosome segregation during mitosis. It connects the kinase Aurora B to the inner centromere allowing this kinase to dynamically access its kinetochore targets. However, the function of its central, 440-residue long intrinsically disordered region (IDR) and its multiple phosphorylation sites is unclear. Here, we determined the conformational ensemble of INCENP’s IDR, systematically varying the level of phosphorylation, using all-atom and coarse-grain molecular dynamics simulations. Our simulations show that phosphorylation expands INCENP’s IDR, both locally and globally, mainly by increasing its overall net charge. The disordered region undergoes critical globule-to-coil conformational transitions and the transition temperature non-monotonically depends on the degree of phosphorylation, with a mildly phosphorylated case of neutral net charge featuring the highest collapse propensity. The IDR transitions from a multitude of globular states, accompanied by several specific internal contacts that reduce INCENP length by loop formation, to weakly interacting and highly extended coiled conformations. Phosphorylation critically shifts the population between these two regimes. It thereby influences cohesiveness and phase behavior of INCENP IDR assemblies, a feature presumably relevant for INCENP’s function in the chromosomal passenger complex. Overall, we propose the disordered region of INCENP to act as a phosphorylation-regulated and length-variable component, within the previously defined “dog-leash” model, that thereby regulates how Aurora B reaches its targets for proper chromosome segregation.